PREVALENCE OF DIARRHOEA AND USE OF ORAL REHYDRATION SALT IN CHILDREN OF RURAL AND URBAN AREAS OF PESHAWAR - Gul, Riaz; Tariq, Muhammad; Zeb, Ahmad; Safeer, Muhammad (Journal of Postgraduate Medical Institute, 2011)
Objective : To find out the prevalence of diarrhoea and use of oral rehydration salt (ORS) for the Methodology: Two areas from Peshawar districts, one rural (Palosi) and one urban (academy- town) were selected. Hundred parents from each area were interviewed based on a specially designed questionnaire. The data regarding prevalence of diarrhoea and type and mode of delivery of ORS was collected in addition to educational and socioeconomic background. Results : Prevalence of diarrhoea was found to be more in rural area (27%) as compared to urban area (16%). Use of ORS was more in urban area (99%) as compared to rural area (40%). Similarly awareness regarding use of ORS was found to be more in urban area (93%) than rural are (32%). Conclusion: Diarrhoea was more common in the rural area while the use of ORS and the awareness regarding use of ORS was more in the urban area. management of diarrhoea in rural and urban areas of Peshawar.